Ribosomal DNA copy number is associated with P53 status and levels of heavy metals in gastrectomy specimens from gastric cancer patients. (May 2020) - Feng, Lingfang; Du, Jing; Yao, Chunji; Jiang, Zhaoqiang; Li, Tao; Zhang, Quan; Guo, Xinnian; Yu, Min; Xia, Hailing; Shi, Li; Jia, Junlin; Tong, Yan; et al.
Highlights: The 45S and 5S rDNA was amplificated in gastric tumor tissues. The copy number of 45S rDNA was significantly elevated in P53 positive patients. The rDNA variation in tumor tissues was associated with metal levels. Abstract: The ribosomal DNA (rDNA) can act as a sensor and responder of cancer-associated stress. Here we investigated rDNA copy number in gastric cancers and its association with existing biomarkers and metals exposure. This study was performed on paired tumor and adjacent normal tissues obtained from 65 gastric cancer patients who underwent gastrectomy. Immunohistochemistry was used to assess HER-2, E-cadherin, EGFR, CK (pan), CK20, CK7, TopoⅡ, CAM5.2, P53, and Ki-67 expression. Inductively coupled plasma mass spectrometry (ICP-MS) was used to detect the concentrations of 17 metals in gastric tissues. rDNA copy number was detected by qPCR in genomic DNA isolated from tissue samples. Associations between the expression of existing markers, metal concentrations, and rDNA copy number were evaluated. Within patients with gastric cancer, the copy number of the 45S rDNA components (18S, 5.8S, 28S) and the 5S rDNA in tumor tissues were significantly higher than those in adjacent normal tissues, whereas mitochondrial DNA (mtDNA) copy number was significantly lower in tumor tissues than that in adjacent normal tissues. Further analysis revealed that the increase in 18S, 5.8S, and 28S rDNA copy number in tumor tissues was diminished in the context of EGFR and P53 loss. Moreover, analysis of metals revealed particularly high concentrations of As, Cd, Cr, Cu and Fe in the gastric tissues of these patients. Intriguingly, rDNA copy number variation across individuals was correlated with the concentrations of some metals. The rDNA was amplified in tumor tissues of gastric cancer patients, and its amplification may be associated with metals exposure. The expression of EGFR and P53 may influence rDNA copy number, with diminished amplification of the rDNA in cancers that were negative for these biomarkers. Our observation further our understanding of rDNA copy number in gastric cancer and its potential as a simple and useful marker in gastric cancer monitoring.